(untitled) (Fiep Bulletin - online, 2012)
The aging process involves several aspects such as social, political, economic and physical. There are factors that have influenced to the growing number of elderly, which increased life expectancy, but the care given to those not kept such evolution, which caught the purpose of reflection. The main objective was to highlight the phenomenon for the aging nursing work in primary care from a pragmatic look, trying to identify which components of nursing practice can be developed with a view to providing an old age assistance. It is a reflection on the care offered to the elderly. Using the available literature in books, articles, and texts from the Internet, works privilege to come support the evolution of man and his need of care, noting that nursing requires a keen sense with this new clientele that swells in humanity. We realized that the elderly population advances in number and longevity and few activities for this demand ahead, will be as required as nursing care.